The cost offsets and cost–effectiveness associated with pegylated drugs: a review of the literature. (December 2012) - Becker, Russell; Dembek, Carole; White, Leigh Ann; Garrison, Louis P
Pegylation (PEG) is used as both a drug-delivery and a drug-modification technology in ten drugs approved by the US FDA. Benefits of PEG drugs can include increased plasma half-life, longer absorption, improved tumor targeting and less antigenicity and immunogenicity. Clinical benefits of PEG drugs over non-PEG drugs may include reduced administration, improved efficacy, improved tolerability, and decreased severity and incidence of adverse events. This study reviews 36 economic literature publications featuring PEG drugs versus non-PEG versions. PEG drugs showed some reductions in overall costs resulting from various offsets including fewer administrations, lower adverse event treatment costs, reduced disease complication costs or reduced inpatient/outpatient costs. Of the 18 cost–effectiveness studies reviewed, 17 of them found PEG drugs to be cost effective versus the non-PEG drugs. Cost offsets and cost–effectiveness of PEG drugs have been demonstrated in multiple studies across various therapies, indications and country settings, and the results have been found to be stable when key parameters were varied in analyses. Further studies are needed to assess the potential for cost savings and cost–effectiveness for new PEG therapies in development.